Functionalization of Carbon Microspheres Using 3-Methacryloxypropyl Trimethoxysilane and its Theoretical Elucidation - Zhao, X.X.; Zhao, H.J.; Li, S.; Yang, Y.Z.; Yang, Z.; Liu, X.G. (Asian Journal of Chemistry, 2013)
Carbon microspheres were oxidized by a mixture of concentrated sulfuric and nitric acids. Then oxidized carbon microspheres were modified by 3-methacryloxypropyl trimethoxysilane (KH-570) to prepare surface molecularly imprinted polymer for adsorbing dibenzothiophene. The effects of reaction time, KH-570 content and the ratio of ethanol to water on silanization were discussed. The morphologies and microstructures of all the samples were characterized by Fourier transform infrared spectrometry, field emission scanning electron microscopy, X-ray photoelectron spectroscopy and thermogravimetry. By virtue of the active sites on carbon microspheres, KH-570 with the double bonds was grafted onto the surface of carbon microspheres, with the optimum parameters: 0.3 g of oxidized carbon microspheres, 1.0 mL of KH-570, reaction for 2 h at 65 ºC, pH » 5, 60 mL of ethanol + water (3:1, v/v). The dispersion of carbon microspheres in ethanol was also improved. The possible reaction mechanism was discussed on the basis of the density functional theory study. This lays an experimental and theoretical foundation for further application of functionalized carbon microspheres.